Pengaruh Marketing digital, Brand image, dan E-WOM Terhadap Keputusan Pembelian Produk Finally Found You Pada TikTok Shop di Kota Batam - Fiona Frederica; Muhammad Haldy (Komunitas Dosen Indonesia, 2026)
The development of social media-based electronic commerce, particularly through the TikTok Shop platform, encourages business actors to implement effective advertising strategies to influence consumers’ purchasing decisions. TikTok Shop has become one of the most widely used platforms due to its ability to integrate entertainment content, promotion, and transactions directly, thereby providing an interactive shopping experience for consumers. The purpose of this study is to examine the effects of Digital Marketing, Brand image, and E-WOM on purchasing decisions of Finally Found You products on TikTok Shop in Batam City. This study utilizes a quantitative methodology, with data gathered via questionnaires administered to 120 respondents. The data were subsequently analyzed utilizing SPSS to investigate the relationships among the research variables. The results indicate that Digital Marketing, Brand image, and E-WOM each have a positive and statistically significant effect on consumers’ purchasing decisions. Furthermore, these three variables simultaneously have a positive and positive and substantial impact on purchasing decisions.. These findings suggest that effective digital marketing management, a strong brand image, and positive E-WOM play an important role in enhancing purchasing decisions and strengthening a company’s competitiveness on the TikTok Shop platform.